Risks of stroke and mortality associated with suboptimal anticoagulation in atrial fibrillation patients - Gallagher, A M; Setakis, E; Plumb, J M; Clemens, A; van Staa, T-P (Thrombosis and haemostasis, 2011)
Atrial fibrillation (AF) carries an increased risk of ischaemic stroke, and oral anticoagulation with warfarin can reduce this risk. The objective of this study was to evaluate the association between time in therapeutic International Normalised Ratio (INR) range when receiving warfarin and the risk of stroke and mortality. The study cohort included AF patients aged 40 years and older included in the UK General Practice Research Database. For patients treated with warfarin we computed the percentage of follow-up time spent within therapeutic range. Cox regression was used to assess the association between INR and outcomes while controlling for patient demographics, health status and concomitant medication. The study population included 27,458 warfarin-treated (with at least 3 INR measurements) and 10,449 patients not treated with antithrombotic therapy. Overall the warfarin users spent 63% of their time within therapeutic range (TTR). This percentage did not vary substantially by age, sex and CHA2DS2-VASc score. Patients who spent at least 70% of time within therapeutic range had a 79% reduced risk of stroke compared to patients with ≤30% of time in range (adjusted relative rate of 0.21; 95% confidence interval 0.18-0.25). Mortality rates were also significantly lower with at least 70% of time spent within therapeutic range. In conclusion, good anticoagulation control was associated with a reduction in the risk of stroke.